Cancer LncRNA Census reveals evidence for deep functional conservation of long noncoding RNAs in tumorigenesis - Carlevaro-Fita, Joana; Lanzós, Andrés; Feuerbach, Lars; Hong, Chen; Mas-Ponte, David; Pedersen, Jakob Skou; Johnson, Rory (Communications biology, 2020)
Joana Carlevaro-Fita, Andrés Lanzós et al. present the Cancer LncRNA Census (CLC), a manually curated dataset of 122 long noncoding RNAs (lncRNAs) with experimentally-validated functions in cancer based on data from the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium. CLC lncRNAs have unique gene features, and a number display evidence for cancer-driving functions that are conserved from humans to mice.
Gesehen am 16.04.2020